Locking plate versus K-wires and cast fixation in lateral closing-wedge osteotomy for cubitus varus deformity - Liu, Jianghua; He, Youzhi; Shi, Qiang; Wang, Yongfu (Frontiers in Pediatrics, 2024)
The aim of this study was to assess the clinical and radiographic outcomes of cubitus varus treatments based on different fixation methods: Locking plate versus Kirschner-wires (K-wires) and cast fixation.Methods: This retrospective study of 28 patients was performed in lateral-wedge osteotomy for cubitus varus deformity in our hospital from July 2018 to July 2020. 14 patients in group A were treated by locking plate after lateral closing-wedge osteotomy, whereas other 14 patients were treated by K-wires in group B. We measured the bony union and